2020
DOI: 10.1002/dc.24615
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic features of a case of mixed medullary and follicular cell‐derived thyroid carcinoma with review of the literature

Abstract: Mixed medullary and follicular cell‐derived thyroid carcinoma (MMFTC) is a rare primary thyroid carcinoma with morphologic and immunophenotypic evidence of admixed parafollicular and follicular cell‐derived tumor populations within the same tumor. We herein present the fine‐needle aspiration biopsy (FNAB) cytology of a case of MMFTC that was diagnosed histologically and discuss potential clues to the diagnosis for cytologists. We also provide a literature review of this uncommon primary thyroid tumor. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Fine needle aspiration (FNA) usually diagnosed PTC or suspicious carcinoma. FNA cytology is thought to be of little diagnostic value in patients with MTC combined with PTC, as it is not easy to detect both pathological types of thyroid cancer (14)(15)(16)(17)(18)(19). The results of FNA in our center were similar to previous studies.…”
Section: Clinical Features and Diagnosissupporting
confidence: 80%
“…Fine needle aspiration (FNA) usually diagnosed PTC or suspicious carcinoma. FNA cytology is thought to be of little diagnostic value in patients with MTC combined with PTC, as it is not easy to detect both pathological types of thyroid cancer (14)(15)(16)(17)(18)(19). The results of FNA in our center were similar to previous studies.…”
Section: Clinical Features and Diagnosissupporting
confidence: 80%
“…The simultaneous occurrence of MTC and papillary thyroid carcinoma (PTC) is a rare phenomenon. PTC has not been reported as part of the MEN syndromes, although MTC with PTC has been reported in nearly 100 cases in the literature 15–24 . MTC originates from parafollicular calcitonin-producing cells; conversely, PTC derives from thyroglobulin-producing follicular cells with different histogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…PTC has not been reported as part of the MEN syndromes, although MTC with PTC has been reported in nearly 100 cases in the literature. [15][16][17][18][19][20][21][22][23][24] MTC originates from parafollicular calcitonin-producing cells; conversely, PTC derives from thyroglobulin-producing follicular cells with different histogenesis. This simultaneous occurrence can be either as a mixed tumor (composed of MTC and PTC tumor populations within a single lesion) or as a concurrent tumor (spatially different tumors with well-defined components).…”
Section: Medullary Thyroid Carcinoma and Papillary Thyroid Carcinomamentioning
confidence: 99%
“…According to a review by Ryan et al in2015, only 444 thyroid collision tumors were reported in the literature [8] . In our study, 61 STC met the definition of thyroid collision tumor.Previous clinical reports on mixed thyroid carcinoma were mostly medullary-follicular carcinoma [11,17,18] .Mixed medullary and follicular cell-derived thyroid carcinoma(MMFTC) is a rare primary thyroid carcinoma composed of admixed parafollicular and follicular cell-derived tumor populations within a single lesion. MMFTC was recognized in the World Health Organization (WHO) Classification of Tumors of Endocrine Organs for the first time in 2004 and the current fourth edition classification (2017) reports <60 cases [11] .In addition, mixed papillary and follicular carcinoma(MPFTC),mixed squamous cell and follicular carcinoma ,mixed anaplastic carcinoma of the thyroid with papillary carcinoma (MAPTC)and Other types of mixed thyroid carcinoma are also occasionally reported [12,19,20] , we found 7 mixed thyroid carcinomas, including 3 MMTC, 1MAPTC, and 1 MPFTC, 1 mixed papillary and poorly differentiated thyroid carcinoma, 1 mixed papillary thyroid carcinoma and squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Such reports have aroused extensive discussion, and since then, the coexistence of multiple different types of thyroid cancer has gradually been reported and recognized. To date, the cases of synchronous squamous cell carcinoma of thyroid(SCCT), papillary(PTC), follicular(FTC), medullary(MTC), poorly differentiated(PDTC) and anaplastic(ATC) thyroid carcinomas have been reported, and both coexisting forms of thyroid cancer have also been implicated [5,[8][9][10][11][12] . However, due to factors such as rare cases and limited conditions, there are few clinical studies on the clinicopathological characteristics and prognosis of multiple synchronous, distinct subtypes of primary thyroid carcinoma.…”
Section: Introductionmentioning
confidence: 99%